Foreign Experiences to Improve the Quality of Education in Non-State Educational Institutions (Journal of Pedagogical Inventions and Practices, 2022)
The article briefly analyzes the structure, experience and modern educational programs of advanced foreign education systems such as Japan, Germany, France, USA. Modern society requires non-governmental educational institutions based on innovations to train qualified specialists. Therefore, the issue of the quality of education of students in schools is crucial in terms of education reform.